PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI UNTUK MENINGKATAN HASIL BELAJAR KIMIA PADA MATERI HIDROKARBON - Rosniar, (Jurnal Serambi Ilmu, 2024)
The purpose of this research was to improve learning achievement of students through the implementation of learning cooperatif model type TAI in Hydrocarbon concept. And to improve learning activities of student through the implementation of learning cooperatif model type TAI in Hydrocarbon lesson. This research was a classroom action research with two cycle. The subjecof this research were 25 students of class X-2 MAN Rukoh Banda Aceh. The data was collected through providing learning achievement of students and observation of students’ activity. That data was analysed using presentage method. Based on the research reslut was implementation of learning cooperatif model type TAI could improve the learning achievement of student in cycle I and Cycle II. It could be seen from the results of research showing 40% of students had passed learning in cycle I and 92% in cycle II. Based the result of study, it is can be conclude that the implementation of learning cooperatif model type TAI can improve learning achievement of students and could improve learning activities of student in Hydrocarbon lesson.